Transcatheter aortic valve implantation: where are we now?. (November 2017) - Mariathas, Mark; Rawlins, John; Curzen, Nick
Transcatheter aortic valve implantation (TAVI) was first used in clinical practice in 2002. Since 2002, there has been a rapid increase in TAVI activity in patients with symptomatic severe aortic stenosis. This has been supported by systematic randomized data comparing TAVI against the gold standard treatment for the last 50 years' surgical aortic valve replacement. TAVI is now currently a recommended therapeutic intervention in the treatment of severe aortic stenosis patients who are deemed either high risk or inoperable. The indications for TAVI continue to expand. Within this review we will focus on the current guidelines for TAVI, the evidence for it, the complications of TAVI, postprocedure care, the technology available to clinicians now and finally the future perspectives for TAVI.